GASTROPROTECTIVE EFFECT OF HYDROALCOHOLIC LEAVES EXTRACT OF PONGAMIA PINNATA - MAHENDRA A. GIRI; RASIKA D. BHALKE; SUBODH C.PAL (International Journal of Pharma and Bio Sciences, 2010)
Pongamia pinnata has long been used in folk medicine in treatment for bronchitis, whooping cough, rheumatic arthritis, and diabetes, various inflammatory conditions and dyspepsia. Therefore, Present study was designed to investigate the antiulcer effect of hydroalcoholic extract of leaves of P. pinnata (HLEPP) using different models of gastric ulceration in rats. Hydroalcoholic extract of leaves of P. pinnata (HLEPP) was subjected to preliminary phytochemical screening. Acute gastric ulceration in rats was produced by oral administration of various noxious chemicals including aspirin or ethanol or indomethacin or pylorus-ligated technique. Gastric tissue was also examined histologically. HLEPP was administered in the dose of 400 mg/kg orally in all experiments; dose was calculated on the basis of acute toxicity study. Omeprazole, ranitidine, misoprostol were used as a reference drug. The antiulcer activity was assessed by determining and comparing the ulcer index in the test drug group with that of the vehicle (negative) control group and standard (positive) control group. The qualitative phytochemical study reveals the presence of alkaloids, carbohydrates, phytosterols, saponnins, tannins and flavonoids. HLEPP at the dose of 400 mg/kg produced a significant (P < 0.05) reduction in the ulcer index. HLEPP significantly inhibited gastric mucosal damage induced by aspirin, ethanol, and indomethacin and in pylorus-ligated rats. The anti-ulcer effect was further confirmed histologically. The anti-ulcer activity of HLEPP was however, less than that of standard drugs. Moreover, further insight into the precise mechanism of action is essential to exploit the complete potency of HLEPP and increase its usage in contemporary medicine. The above effects of HLEPP may also be due to the presence of tannins and flavonoids in the extract.